To prevent or pursue displacement? - Barrs, C (Refugee Studies Centre, University of Oxford, 2012)
The repertoire of survival actions of at-risk civilians includes both avoiding and attempting displacement. But there are also overlaps, combinations and tacking back and forth between the two, while trying to mitigate the risks that any choice entails.